Personal Branding in the Digital Era: Social Media Strategies for Graduates - Kanasan, Muthukumaran (Journal of Communication, 2024)
Purpose: This study represented an important effort to delve into the dynamics of personal branding on social media and its impact on the career trajectories of graduates. Methodology: By adopting a quantitative approach through a questionnaire-based survey from 280 respondents, the research sought to gather empirical data that could shed light on the patterns and trends associated with personal branding practices among this demographic. By designing survey questions aligned with the research objectives, the study aimed to capture a comprehensive picture of how graduates utilized social media for personal branding and how this activity correlated with their career advancement. Findings: The results showed a noticeable and meaningful connection, with a correlation coefficient (r-value) of 0.707, indicating statistical significance (p = 0.05). This indicated a robust relationship between the variables under examination. The strong correlation underscored the importance of personal branding on social media in assisting graduates with their job search endeavors on these platforms. This capability allowed them to establish direct connections with recruiters and improve their career opportunities significantly. Additionally, the rapidly evolving nature of social media platforms may have introduced complexities in capturing the most current trends and practices related to personal branding. Unique contribution to Theory, Practice and Policy: Symbolic Interactionism theory can be used to examine the idea of personal branding and how people utilize social media to present themselves and shape perceptions. Moreover, this theory could prove beneficial for future researchers or scholars keen on delving into related themes, providing a fundamental reference for their investigations. The research proposed a variety of suggestions that could enhance understanding regarding the personal branding strategies that help graduates achieve their professional goals. These recommendations encompass recognizing the importance for recruiters, gaining insights into graduates' online activities, and grasping candidates' skills and interests, all of which are essential for recruiters to make well-informed choices and extend invitations to potential team members.